Accounting executives, perception on the relevance of UiTM accounting courses towards an accounting career / Zuraini Yaacob ... [et al.] - Yaacob, Zuraini; Awang, Norasmila; Said, Roshima; Abdul Rahman, Nor Hafizah (2006)
Many researchers have debated the relevance of accounting curriculum to an accounting career. Globalisation and the revolution in information technology have necessitated the revision of the accounting curriculum continuously to meet the new challenges. There have been complaints that students entering the accounting profession have weak communication and problem-solving skills. The university accounting programs have been blamed for failing to recognize the extensive changes taking place in technology, society values, social, government, and business institutions. The present study seeks to ascertain the perceptions of the accounting executives on the relevance of the courses in Bachelor of Accountancy (UiTM) towards accounting career. The findings indicate that the Practical Training has been perceived as Very Relevant by all the respondents. The courses that have been ranked the highest (total mean score above 3.7) by all the respondents were Principle of Accounting 2, Cost and Management Accounting, Financial Management, Financial Reporting 1, Management Accounting & Control, Public Sector Accounting and Financial Reporting 2. For the non-accounting subjects Communication & Negotiation in the Workplace and Speech Communication were perceived as Very Relevant. The other non-accounting courses that were ranked highly (total mean score above 3.5) were Business Management, Management Theories and Practice, Commercial Law, Corporate Finance, Strategic Management and Risk Management. On the other hand, the top two courses as ranked by the financial accountants were Practical Training and Cost and Management Accounting. Meanwhile, the management accountants placed the top two rankings for Practical Training and Management Accounting & Control. The auditor placed first rankings (with similar mean value) for Financial Reporting, Public Sector Accounting, Management Accounting & Performance Evaluation and Accounting Theory and Practice. For the elective courses 1 and 2, the financial accountants picked Advance Public Sector Accounting, Internal Auditing, Risk Management and International Financial Management as the most relevant. Meanwhile, the management accountants choose Organisational Behaviour and Risk Management as the most relevant. On the other hand, the auditors choose Advance Public Sector Accounting, Marketing Services, Human Resource Management, Education Psychology and International Accounting as the most relevant.